Antiobesity activity of aqueous and ethanol extracts of Enicostemma littorale in high fat diet induced obese rats - Ankur garg,; Dr Randhir Singh, (International Journal of Phytomedicine, 2014)
Obesity is a chronic disorder of global prevalence and associated with morbidity and mortality. Therefore, attention is being focused on the investigation of plant-based drugs used in the traditional medicine for the treatment of obesity. The presents work evaluates the anti-lipase and antiobesity activity of ethanol and aqueous extracts of Enicostemma littorale (ElEe & ElAe) (Genitanaceae) (Synonym – Enicostemma axillare) in HFD induced obesity in rats. Male Wistar rats weighing 150-200 g were divided into different group’s i.e. Normal control, HFD control, Orlistat (lipase inhibitor), ElEe & ElAe at doses of 200, 400, 250 and 500 mg/kg p.o. Treatment was started after 6 weeks upto 12 weeks alongwith HFD (except normal control). Oxidative stress was measured by measuring MDA, SOD and GSH level. Obesity was assessed by measuring morphological parameters, serum glucose, serum cholesterol, triglycerides and HDL level. ElEe & ElAe at 200, 400, 250 and 500 mg/kg/orally significantly attenuated morphological parameters i.e. weight gain, BMI, WHR, obesity index and adiposity index respectively as compare to HFD control group. Similarly, serum glucose, triglyceride, total cholesterol and oxidative stress were found to be attenuated as compare to HFD control group. The aqueous and ethanol extracts of Enicostemma littorale exhibit significant anti-lipase and antiobesity activity in high fat diet induced obesity in rats.